ANTARTIC: WAIS THAWING AND VOLCANISM - Ferrando, Francisco (Revista Geográfica del Sur, 2020)
and faster loss of mass in the western sector of the Antarctic Ice Sheet (WAIS), which hasin some of them has reached magnitudes not recorded for thousands of years (Domacket al., 2002). Beyond the effects of the global warming and direct human impact, thisparticularly high reduction in WAIS led to the consideration of another genetic factor,namely volcanism and the associated latent heat at the base of the ice mass.During research carried out on King George Island, a strong retreat and thinning ofactivity, such as volcanic necks, lava fragments and pyroclasts, were found (Kellemetals,in and around the South Shetland archipelago (Krauss, 2008; Ferrando et al., 2009),led an investigation using satellite images in the Mary Byrd Land sector. As a result,several volcanic structures were recognized in that sector of the WAIS. Consequently, aseveral researchers found a large number of volcanic structures, some of them active inthe Mary Byrd Land and its surroundings, and some others, such as the existence of rockyglaciers at the McMurdo dry valleys (Bockheim, 2002), reveal a double cause for theunequal level of consumption between WAIS and the eastern sector of Antarctica (EAIS).Additionally, recent studies have established that WAIS is the most volcanic territory on theplanet. This background leaves no doubts about the role of volcanism in the greater lossof ice from WAIS than from EAIS,in the greater loss of thickness and in the accelerationof glaciers. El objetivo de esta investigación fue encontrar una explicación para la diferente y más rápida pérdida de masa del sector occidental de la Antártica o WAIS, lo cual se ha estado reflejando en desprendimientos masivos de los glaciares litorales, pérdida de espesor e incremento de la velocidad, lo cual en algunos de ellos ha alcanzado magnitudes no registradas hace miles de años (Domacket al., 2002). Más allá de los efectos del calentamiento global y del impacto humano directo, esta particularmente alta reducción del WAIS llevó a pensar en la concurrencia de otro ...